Philosophy in today's society: is it obsolete or does it still have value? - Mora Ramirez, Rafael F. (2024)
A reflection on the current relevance of philosophy is presented, contrasting the anti-philosophical positions with those that promote this type of discipline. It is mentioned that philosophy is not only a type of knowledge, but also represents a journey through ideas that a subject makes to find unity in reality. Likewise, the role of philosophy in some historical-revolutionary processes is considered relevant. It is pointed out that there is a crisis marked by the current tendency towards simplification and the search for quick results. However, philosophy is reflective, profound and seems to be opposed to mercantile interests since it does not seek immediate objectives. This paper raises arguments against philosophy such as the idea that it is an abstract, unintelligible activity, dangerous for youth as it encou- rages rebelliousness and socially has less value than any form of entertainment. On the other hand, there are also arguments in favor of philosophy, highlighting its questioning capacity, its usefulness in facing life's problems, and its role in the cultivation of introspection. Philosophy elaborates social critiques that are necessary to be aware that, in the midst of so much technological progress, there are still people in the world who suffer.